THE INFLUENCE OF LEADERSHIP ON TEACHER’S PERFORMANCE DURING PANDEMIC COVID – 19 - Mutiyawati Mutiyawati (Sensei International Journal of Education and Linguistic, 2021)
The presence of the March 2020 pandemic has changed the way people live, including governance in schools. Online learning is the best option to avoid the widespread spread of covid-19. This pandemic is certainly very influential on the culture shown by school leaders. Strong school culture is a force that can unite goals, create motivation, commitment, and loyalty for all school members, and provide the necessary structure and control without relying on formal bureaucracy. School culture is expected to improve school quality, performance, and quality of life which is expected to have healthy, dynamic or active, positive, and professional characteristics. However, in the implementation process, the principal's leadership and the implementation of school culture are still not optimal, which can be seen in the existing problems and affect the teachers' performance in schools. So the purpose of this study is to determine the contribution of principals' leadership and school culture to teacher performance. This research is an ex-post-facto research type with a correlation study using quantitative research methods. The data collection instrument was carried out using a non-test method in the form of a questionnaire instrument and a documentation study. The results obtained in this study indicate a significant influence between the principal's leadership and school culture on teacher performance.